China Pakistan economic corridor (CPEC), its role in Pakistan economy and its social and environmental status. - Arshed, Noman; Awan, Mahak Zahra; Mirza, Aaiza; Riaz, Faheem; Shabeer, Muhammad Ghulam (Journal of Applied Research and Multidisciplinary Studies, 2022)
China Pakistan Economic Corridor (CPEC) is a plan to kick start practical cooperation between China and Pakistan, as well as support China and the rest of West Central, which is expected to propel Pakistan’s and China’s already strong relationship to new heights. Hope for economic transformation and assistance in overcoming Pakistan’s power shortage. The strategic significance of CPEC must be described and studied from various historical, economic, cultural, and political perspectives. As it aims to construct a network of roads, highways, and railways from Khunjerab, Pakistan’s border with China to Gwadar. So, this initiative presents a significant opportunity for Pakistan’s economic growth. Because of its depth, Gwadar is an important port. This article emphasizes the economic status of Pakistan influenced by CPEC, the effect of its infrastructure on GDP growth, Impact on trade and the revenue generated. Moreover, the effect of CPEC on the social and environmental aspects is also explained.